2018
DOI: 10.1097/eja.0000000000000776
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine as a part of general anaesthesia for caesarean delivery in patients with pre-eclampsia

Abstract: Pan African Clinical Trial Registry (PACTR201706002303170), (www.pactr.org).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Administration of dexmedetomidine, a sedative affecting the α2 adrenaline receptor, which is commonly used in intensive care, has been shown to improve survival and to preserve eGC in a rat heatstroke model [119]. There is some evidence that administration of dexmedetomidine in pre-eclamptic patients was associated with hemodynamic and hormonal stability, without causing severe adverse neonatal outcomes [120][121][122][123].…”
Section: Metforminmentioning
confidence: 99%
“…Administration of dexmedetomidine, a sedative affecting the α2 adrenaline receptor, which is commonly used in intensive care, has been shown to improve survival and to preserve eGC in a rat heatstroke model [119]. There is some evidence that administration of dexmedetomidine in pre-eclamptic patients was associated with hemodynamic and hormonal stability, without causing severe adverse neonatal outcomes [120][121][122][123].…”
Section: Metforminmentioning
confidence: 99%
“…In ICU patients, similar values were found, with half-lives ranging from 2.2 to 3.7 h (ref. 16,17 ). In this study, dexmedetomidine enhanced analgesia, decreased VAS, and reduced tramadol consumption at 3 h postoperatively.…”
Section: The Effects Of Dexmedetomidine On Maternal Postoperative Anamentioning
confidence: 49%
“…Furthermore, studies demonstrated that the complications, such as maternal bradyarrhythmia and hypotension, were not reported during cesarean section 1,5. Likewise, in the trail of Eskandr et al,11 no patients required ephedrine but four required atropine (three in dexmedetomidine group, one in control group); however, these differences were not statistically significant. However, Yu et al13 described one patient in the dexmedetomidine group and two patients in the control group were treated with ephedrine.…”
Section: Resultsmentioning
confidence: 95%
“…Adequate blinding of outcome assessment was found in four trials,10,13,21,22 while it was inadequate in two trials 12,23. Seven trials1012,20–23 had low risk of incomplete outcome data, and there was also a low risk of reporting bias in seven trials 1113,20–23. (Figure 3).…”
Section: Resultsmentioning
confidence: 99%